2006
DOI: 10.1002/bit.21013
|View full text |Cite
|
Sign up to set email alerts
|

Process parameter shifting: Part I. Effect of DOT, pH, and temperature on the performance of Epo‐Fc expressing CHO cells cultivated in controlled batch bioreactors

Abstract: The impact of process environment changes on process performance is one of the most crucial process safety issues when cultivating mammalian cells in a bioreactor. In contrast, directed shifting of process parameters can also be used as an optimization tool providing higher cell and product yields. Compared to other strategies that also aim on the regulation of cell growth and protein expression process parameter shifts can be easily performed without reagent addition or even genetic modification of the host c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
149
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 49 publications
17
149
3
Order By: Relevance
“…For example, the Sixfors multireactor system (Infors AG, Bottmingen, Switzerland) was used by Trummer et al [8] to investigate the effect of variation in DOT, pH, and temperature (T) on cell growth, metabolism, and cell cycle distribution. The authors observed that the reduction of T and pH exert the most significant effects on process performance mainly by reducing cell growth and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Sixfors multireactor system (Infors AG, Bottmingen, Switzerland) was used by Trummer et al [8] to investigate the effect of variation in DOT, pH, and temperature (T) on cell growth, metabolism, and cell cycle distribution. The authors observed that the reduction of T and pH exert the most significant effects on process performance mainly by reducing cell growth and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that growth arrest was not related to oxygen depletion, dissolved oxygen was measured during the experiments. The dissolved oxygen in all the cultures ranged between 40-80% (Figure 7.3), which is sufficient for the cell growth and not in the limiting range that can lead to conditions of hypoxia (Ozturk and Palsson, 1990b;Shu and Liao, 2002;Trummer et al, 2006). Figure 7.4A shows the time evolution of mAb concentration in each different volume.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the model can be coupled to a glycosylation model [80] in order to capture product quality concerns. Several studies have reported changes [81][82][83][84], even improvements, on the glycosylation patterns linked to the cell culture environment (e.g. temperature, pH).…”
Section: Discussionmentioning
confidence: 99%